2002
DOI: 10.1097/00007890-200203150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of normothermic perfusion over cold storage in liver preservation

Abstract: Normothermic sanguineous oxygenated perfusion is a superior method of preservation compared with simple cold storage in UW solution. In addition, perfusion allows the possibility to assess viability of the graft before transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
176
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(189 citation statements)
references
References 27 publications
9
176
1
3
Order By: Relevance
“…However, there is an obvious problem that recipients are greatly more than donors. The disparity between the increasing demand for liver donors and the limited supply of donor organs has led to a reconsideration of the use of marginal pools, such as NHBD [25][26][27] . NHBD programs have been used successfully in kidney transplantation, and were able to increase donor pool of kidneys by 40%.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an obvious problem that recipients are greatly more than donors. The disparity between the increasing demand for liver donors and the limited supply of donor organs has led to a reconsideration of the use of marginal pools, such as NHBD [25][26][27] . NHBD programs have been used successfully in kidney transplantation, and were able to increase donor pool of kidneys by 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the advantage of NMP over CS in the preservation of DCD livers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), suggesting that NMP may greatly benefit the practice of liver transplantation. conducted using whole blood (WB) (9)(10)(11)(19)(20)(21). The same group recently introduced NMP in human liver transplantation using blood and additives during perfusion (18).…”
Section: Introductionmentioning
confidence: 99%
“…These data are mainly based on organ retrieval, preservation, ex-situ-evaluation and transplantation in large animal models (pigs). In the experimental setting normothermic perfusion has been shown to resuscitate porcine livers subjected to 60 to 90 minutes of warm ischaemia [14,29]. Warm perfusion has the added advantage of allowing more effective viability assessment of the organs while on the circuit (using multiple perfusion dynamic and biochemical parameters), contrasting with the more limited parameters available on the hypothermic circuit [27].…”
Section: Normothermic Machine Perfusion (Nmp)mentioning
confidence: 99%
“…The initial preservation experiments were carried out to compare preservation by warm perfusion with conventional cold preservation [29]. Porcine livers were retrieved and stored for a period of 24 hours, either flushed with UW solution and placed in an icebox or attached immediately to the preservation circuit.…”
Section: Preclinical Investigationsmentioning
confidence: 99%